Asia is the mine of natural antiviral products for public health. - R.R., Hafidh; Abdulamir, Ahmed Sahib; Jahan Shiri, Fatemah; Abas, Faridah; Abu Bakar, Fatimah; Sekawi, Zamberi (Bentham Open, 2009)
This review highlights a wide range of research on antiviral natural products in Asia in the period from 2000 to 2008. It focuses on the most important findings in this field specifically on the plants' components with potential antiviral activity against wide range of pathogenic DNA and RNA viruses. In addition, the difference between Asians and other populations regarding their habits of using natural products containing antiviral activity instead of allopathic medicine has been reviewed briefly. In conclusion, Asian continent serves as the most important source for providing the candidate natural products for the future antiviral drugs which could save the lives of millions in the world.